Fibonacci Polynomials and It’s Generalization - Kumar, Nand Kishor; Sahani, Suresh Kumar (Mikailalsys Journal of Mathematics and Statistics, 2025)
This article explores the definition, properties, and generalizations of Fibonacci polynomials, providing a comprehensive understanding of their mathematical significance. We have used their Binet’s formula and generating function to derive the identities.